Trese last seen after midnight - Tan, Ferdinand-Benedict G.; Baldisimo, Jonathan A. (Pasay City Visprint, 2011)
A horror/crime comic book series. Trese is also the name of the heroine who manages to fight the bad demons and solve these mysteries together with her able bodyguards.
Cadena de Amor -- A private collection -- Wanted: bedspacer -- Fight of the year.
Graphic novel.
"Foul play, magic spells, supernatural criminals. When crime takes a turn for the weird, the police call Alexandra Trese."--Cover
Fi-17257g donated by Ms. Jowana B. Bueser, BA Sociology, 2000 CAS, UPLB
Keywords: Horror tales; Paranormal fiction; Murder -- Fiction